فهم محركات النزوح طويل الأمد - Kraler, A; Etzold, B; Ferreira, N (Refugee Studies Centre, University of Oxford, 2021)
يمكن أن تقدم حركة تنقل النازحين وشبكات علاقاتهم العابرة للحدود المحلية موارد مهمة في البحث عن حلول دائمة. Displaced persons’ mobility and their translocal networks can provide important resources in the search for durable solutions.